PERANCANGAN APLIKASI WHISTLE BLOWING DI INSPEKTORAT KOTA LUBUKLINGGAU: PERANCANGAN APLIKASI WHISTLE BLOWING DI INSPEKTORAT KOTA LUBUKLINGGAU - Primadasa, Yogi (Universitas Lembah Dempo, 2022)
The Lubuklinggau City Inspectorate is one of the elements of APIP in the area which is one of the inspectorates that has reached level 3 on APIP Capability in 2019 from the Financial and Development Supervisory Agency (BPKP). The predicate level 3 APIP Capability obtained by the Lubuklinggau City Inspectorate is a prestigious achievement, where there are only 4 (four) Regency/City Inspectorates in South Sumatra Province who get it. APIP Level 3 capability means that APIP is expected to act as a quality guarantor, overseeing regional strategic objectives and as a consultation that can provide added value to Regional Governments To be able to improve the performance that has been achieved by the Lubuklinggau City Inspectorate, the use of information technology is a necessity to add because information technology can provide value to the internal control function, especially in achieving audit effectiveness and efficiency, and will directly increase audit productivity which has a big impact. for the economy Community service this time is a real form of knowledge transfer to implement an information system that we call the Whistle Blowing System into the regional internal control system in order to overcome the problems faced by the Lubuklinggau city inspectorate, namely to provide convenience in carrying out its functions. supervision, especially in evaluation and reporting